2001
DOI: 10.1046/j.1537-2995.2001.41040522.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion costs by diagnosis‐related groupsin 60 university hospitals in 1995

Abstract: Members of the UHC may utilize such analyses to identify surgical or medical diagnoses with transfusion costs at variance with the group norm. These DRGs could then be targeted for further evaluation of components contributing to high costs, for possible alterations in physician or clinical laboratory practices. Considering those conditions with the highest cumulative transfusion costs (e.g., BMT, liver transplant, acute leukemia, and cardiothoracic procedures), changes in transfusion practices that affect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 20 publications
1
44
0
Order By: Relevance
“…Bleeding is financially costly and associated with worse patient outcomes with 3-fold higher mortality demonstrated in a similar NSTE ACS population (major bleeding, 18.6% vs no bleeding, 5.1%). 21,39,40 We demonstrate that patients who receive excess antithrombotic therapy have higher mortality and longer lengths of stay presumably due to bleeding events. Bleeding also demonstrates a doseresponse with greatest risk among those patients receiving the most excess (major excess) or multiple agents in excess dose.…”
Section: Association Of Dosing With Outcomesmentioning
confidence: 74%
“…Bleeding is financially costly and associated with worse patient outcomes with 3-fold higher mortality demonstrated in a similar NSTE ACS population (major bleeding, 18.6% vs no bleeding, 5.1%). 21,39,40 We demonstrate that patients who receive excess antithrombotic therapy have higher mortality and longer lengths of stay presumably due to bleeding events. Bleeding also demonstrates a doseresponse with greatest risk among those patients receiving the most excess (major excess) or multiple agents in excess dose.…”
Section: Association Of Dosing With Outcomesmentioning
confidence: 74%
“…In fact, the need for transfusion is almost ubiquitous, and in almost all DRGs transfusion can be found. In an analysis carried out in 60 university hospitals in the USA in 1995, Jefferies et al [5] showed that 471 of 486 DRGs had identifiable blood costs. The highest mean costs could be found in the DRG for bone marrow transplant (DRG 481) with USD 6,183.00, followed by liver transplant (DRG 480, USD 5,548.00) and acute leukaemia…”
Section: Challenge 2: Trying To Adequately Remunerate the Treatment Omentioning
confidence: 99%
“…Shrinking donor pools and stringent donor qualification criteria can lead to rising costs and constraints in the supply of blood products [4]. Although in general only about 1% of the total inpatient treatment costs are caused by hemotherapy, this figure can substantially rise in patients requiring frequent transfusions such as in leukaemia treatment, organ transplantation, or obstetrics [5]. Therefore, it is important for hospitals to focus on optimal blood acquisition and to avoid inappropriate blood transfusions [6].…”
Section: Introductionmentioning
confidence: 99%
“…For the remaining, we used either a cost-to-charge ratio for a like item, an average of cost-to-charge ratios for charges within the same class as defined by the first 3-digits of the service code, or the average cost-to-charge ratio calculated for all items. Items utilized in the cost function for each patient are overhead, pharmacy, IV therapy, blood labs, laboratory, and diagnostic imaging (Jeffries et al 2001;Tonato et al 1991). This analysis used the perspective of the payer in making these estimates.…”
Section: Defining Costsmentioning
confidence: 99%
“…Most studies seeking to measure the costs of AEs have focused on the individual AE, such as anemia, neutropenia, thrombocytopenia, mucositis and dehydration (Elting et al 2003;Jeffries et al 2001;Lyman et al 1998;Stewart et al 1999). Clinically, however, AEs present in clusters.…”
Section: Introductionmentioning
confidence: 99%